EPIDEMIOLOGICAL PROFILE AND INJURY MECHANISMS IN POSTOPERATIVE PATIENTS WITH LOWER LIMB TRAUMA (CIPEEX, 2025)
Trauma is one of the leading causes of mortality and disability among young adults, resulting in high medical costs and productivity loss, making it essential to understand its economic and psychological impact to develop effective health policies. This study aimed to investigate the epidemiological profile of patients in the postoperative period following lower limb trauma, such as fractures and ligament ruptures, emphasizing the main mechanisms and types of injuries. This is a cross-sectional study with a quantitative and epidemiological approach, focusing on the profile of lower limb traumas in an orthopedic unit in the central-northern region of Goiás. Data collection was conducted through a sociodemographic questionnaire and included 92 volunteers with a mean age of 39.18 years (±11.28), of whom 68.5% were male and 31.5% were female. Results indicate that 69.6% of cases were fractures, predominantly due to falls and motorcycle accidents, and 29.3% were ligament ruptures, mainly associated with sports. Although the prevalence of injuries was higher in men, statistical analysis showed no significant differences between sexes. These findings highlight the need for preventive strategies for falls, accidents, and sports injuries to improve clinical outcomes and reduce costs associated with orthopedic treatment.
Keywords: Traffic accident; Lower limbs; Epidemiological profile; Postoperative